Hubungan antara Locus of Control dengan Prokrastinasi Akademik pada Mahasiswa Psikologi IAIN Kediri - Moh. Soleh; Moh Irfan Burhani; Luthfi Atmasari (Happiness (Journal of Psychology and Islamic Science), 2020)
The purpose of this study was to determine the relationship between locus of control and academic procrastination in psychology students at IAIN Kediri. This study used a quantitative random sampling method with 68 students as the subject. The measuring instrument used was a locus of control scale with a reliability of 0.958 and academic procrastination with a reliability of 0.893 which was compiled by the researcher. After the sample is given a measuring instrument, the results of statistical calculations with Pearson's product moment analysis show the sig = -0.011 (> r table 0.244) and a determination coefficient of 0.121, which means that the locus of control variable contributes to academic procrastination by 12.1 percent and the rest 87.9% is determined by other factors.